2004
DOI: 10.1677/joe.0.1820257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aqueous extract of Acacia nilotica ssp adansonii on milk production and prolactin release in the rat

Abstract: In view of the traditional belief that Acacia nilotica ssp adansonii (AN) can stimulate milk production in lactating women, experiments were performed to determine the effect of an aqueous extract of AN on milk production in rats. Female rats that received oral doses of aqueous extract of this plant during their first lactation produced about 59% more milk than controls (P<0·01). Pup weight gain was also significantly higher than that in the control group. A lower dose, comparable to that used by women to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 25 publications
0
34
1
2
Order By: Relevance
“…Measuring the milk yield produced by a rat is usually very difficult. However, according to Lompo-Ouedraogo et al [20], it is possible to estimate this quantity of milk produced by carrying out different sessions of weighing of the pups. This method considers the pups as powerful vacuum cleaners capable of completely emptying the contents of the mammary glands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring the milk yield produced by a rat is usually very difficult. However, according to Lompo-Ouedraogo et al [20], it is possible to estimate this quantity of milk produced by carrying out different sessions of weighing of the pups. This method considers the pups as powerful vacuum cleaners capable of completely emptying the contents of the mammary glands.…”
Section: Discussionmentioning
confidence: 99%
“…According to Datti et al [19] and Lompo-Ouedraogo et al [20], the leaves of Hippocratea obtusofolia (Alismataceae) and Acacia nilotica ssp adansonii (Fabaceae) would be capable of inducing galactagogue activities in guinea pigs and rats, respectively. The work of Gbadamosi and Okolosi [21] helped to safeguard traditional knowledge about the use of several galactagogue plants.…”
mentioning
confidence: 99%
“…While, milk protein content did not differ significantly (P>0.05) between treatments (Table 4 and Fig 4). In some reports, it was demonstrated that many plants increased milk production in animals through the induction of lactogenic hormone (prolactin) Lompo-Ouedraogo et al (2004) and Patel and Kanitkar, (1969). Some plants contain estrogenic substances such as anethole that increase the secretion of milk.…”
Section: Milk Yield and Compositionmentioning
confidence: 99%
“…Galactagogues have a profound effect on the mammary secretory cells proliferation which is used as an indicator of lactogenic activity. [21] Hence, the increase of rate of milk secretion in MTLF could be due to mammary secretory cell population and cellular activity. [2223] Milk consumption is responsible for body maintenance and growth of neonates.…”
Section: Discussionmentioning
confidence: 99%